2022
DOI: 10.1021/acs.jafc.2c01975
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of l-Glutamine on High-Fat Diet-Induced Metabolic Disorders Linking with Regulation of Intestinal Barrier Integrity, Hepatic Lipid Metabolism, and Gut Microbiota in Rats

Abstract: The present study was conducted to investigate the effects of l-glutamine (Gln) on a high-fat diet (HFD)-induced lipid metabolic abnormality and explore its possible mechanisms. The results demonstrated that Gln administration reduced body weight, improved serum lipids, and decreased glucose tolerance in HFD-fed rats. Meanwhile, Gln administration alleviated liver injury, reduced the hepatic inflammatory response by inhibiting NLRP3 inflammasome activation, and decreased hepatic lipid accumulation by promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…FATP4 is also believed to play a role in FA uptake, as the knockdown of FATP4 in primary mice's small intestinal epithelial cells resulted in reduced FA uptake [28] . Following absorption by intestinal cells, FAs are transported to the endoplasmic reticulum via microsomal triglyceride transfer protein (MTTP) and then packaged with apolipoproteins (such as ApoB, ApoA-I, and ApoA-IV) to form CM [28,29] . This study found that AVN B can inhibit the expression of CD36, FATP4, and ApoA-IV.…”
Section: Discussionmentioning
confidence: 99%
“…FATP4 is also believed to play a role in FA uptake, as the knockdown of FATP4 in primary mice's small intestinal epithelial cells resulted in reduced FA uptake [28] . Following absorption by intestinal cells, FAs are transported to the endoplasmic reticulum via microsomal triglyceride transfer protein (MTTP) and then packaged with apolipoproteins (such as ApoB, ApoA-I, and ApoA-IV) to form CM [28,29] . This study found that AVN B can inhibit the expression of CD36, FATP4, and ApoA-IV.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, dietary fiber with insulin altered the composition of the microbiota and the levels of microbiota-derived metabolites, notably bile acids, that triggered type 2 inflammation at barrier surfaces [10,26]. Some special diets, such as methionine-restricted diets (MRDs) and l-Glutamine, enhanced the intestinal barrier integrity by regulating the intestinal microbiota and bile acids profiles [27,28]. And a BAR signaling-independent, physicochemical mechanism for conjugated the BA-mediated protection of epithelial barrier function was described.…”
Section: Bile Acids and Gut Microbiotamentioning
confidence: 99%
“…Furthermore, glutamine administration has been shown to suppress inflammation by inhibiting the activation of NLRP3 and modulating cell pyroptosis. [80,81] Zhang et al [82] demonstrated that inhibition of glutaminolysis can inhibit the activation of the NLRP3/caspase-1/IL-1β pathways. The activation of JNK is dependent on the phosphorylation of JNK, while treatment with Gln can decrease the phosphorylated JNK by attenuating inflammation.…”
Section: Inflammationmentioning
confidence: 99%